A new genus with seven species of the Subfamily Nopinae (Araneae, Caponiidae) from the Neotropical region - Sánchez-Ruiz, Alexander; Brescovit, Antonio D. (Zootaxa, 2017)
The new genus Medionops is proposed for a group of caponiid spiders found in South America and Panama. Nops simla Chickering and Nops cesari Dupérré are transferred to this new genus. Additionally, five new species are described: the type species Medionops blades n. sp. from Colombia; Medionops claudiae n. sp., Medionops murici n. sp. and Medionops ramirezi n. sp. from Brazil; and Medionops tabay n. sp. from Venezuela. All of these species belong to the subfamily Nopinae and have the three membranous translucent modifications found in some other nopine genera. However, in this new genus, the ventral translucent keel on the anterior metatarsi (crista herein) is very short, almost unnoticeable or even absent in some species. The translucent extension of the membrane between the anterior metatarsi and tarsi (gladius herein) retains the same shape, but it is absent in M. murici n. sp. Also, Medionops n. gen. species have an unpaired claw on all tarsi, which is elongate and dorsally reflexed, and is associated with a membranous globose translucent lobe (arolium herein); a structure present only in Nops MacLeay and Nopsides Chamberlin. Beside the characteristics mentioned above, members of this new genus differ from other nopine in the shape of labium and endites and in the conformation of male and female genitalia. The three membranous translucent modifications on legs of some nopine genera are discussed and their terminologies are standardized.